Remote-access thyroidectomy with the da Vinci SP system: feasibility in a cadaveric model - Stein, Hubert; Kang, Sang Wook; Heo, Seung Young; Rheinwald, Markus (Frontiers in Surgery, 2023)
Background This study aims to study the feasibility of a remote-access thyroidectomy through presternal and submental approaches with the da Vinci SP system. Methods Bilateral thyroidectomies were performed in five cadaveric models. A single incision in the presternal area was used in two cadavers, and a submental facelift incision approach was used in three cadavers. Results Performing remote-access thyroidectomy was completed with a presternal approach in one cadaver and with the submental approach in three cadavers. The required skin flap development was minimal, and the docking time for the SP system was quick for all procedures. Time to full exposure of the thyroid gland after skin incision was less than 30 min for the presternal approach and less than 27 min for the submental procedure. Completing total thyroidectomies took 83 min in the presternal approach and between 67 and 127 min in the submental access. No additional ports were required to expose the gland and complete the bilateral resection. Conclusions Total thyroidectomy was feasible with the da Vinci SP system in single incision presternal and submental approaches comparing promisingly with other currently applied robotic methods. Further studies will be required to assess whether a presternal or submental thyroidectomy with the da Vinci SP system provides clinical benefits in real patients.